Pengaruh Akomodasi, Transportasi dan Harga Jasa Boga Terhadap Minat Melakukan Perjalanan Wisata: Studi Pada Mahasiswa UIN Sayyid Ali Rahmatullah Tulungagung - Muna, Natasya Lailiya Khoiril; Arosyid, Harun; Saxzena, Bayyu; Yudiantoro, Deny (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to determine the effect of accommodation, transportation and food service prices on interest in travel in Tulungagung. This research is a quantitative study using primary data for 2015-2022 obtained from the Central Bureau of Statistics (BPS). The method used uses quantitative methods with data collection using questionnaires. Based on research that has been conducted on the effect of accommodation, transportation, and the price of food services on interest in travel (case study of Sharia Tourism Study Program Students UIN Sayyid Ali Rahmatullah Tulungagung Class of 2020-2022). Accommodation, Transportation, and Food Service Prices have a positive effect on interest in travel. The higher the level of accommodation, transportation and the price of good food services, the higher the student's interest in trying to travel. Accommodation has a positive effect on interest in travel. The higher the level of accommodation regarding travel interest, the higher the interest in travel will be. Transportation has a positive effect on interest in travel. The higher the level of transportation regarding travel, the higher the interest in travel will be. price of food services has no effect on interest in traveling. The small value of the price of food services does not necessarily attract tourists to travel.